2021
DOI: 10.1080/21655979.2021.1995994
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin alleviates myocardial ischemia/reperfusion injury by regulating the nuclear factor-erythroid factor 2-related factor 2 (Nrf2) /System xc-/ glutathione peroxidase 4 (GPX4) axis to inhibit ferroptosis

Abstract: Ferroptosis is an important form of myocardial cell death in myocardial ischemia-reperfusion injury (MIRI). Naringenin (NAR), as a flavonoid, has a significant advantage in improving MIRI. But the regulatory effect and mechanism of NAR on ferroptosis in MIRI have not been reported. After the rats were given NAR and induced to form myocardial ischemia-reperfusion (MI/R) injury, Tetrazolium chloride (TTC) staining was used to detect the myocardial infarction area of rats, and Hematoxylin-eosin (H&E) staining was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 30 publications
5
83
0
Order By: Relevance
“…For instance, Nrf2 interacts with Pitx2 to repair heart function by stimulating antioxidant signaling [ 40 ]. However, the dysfunction of Nrf2 induces excessive cardiac oxidative stress, senescence, and cell death [ 41 , 42 ]. Therefore, the activation of Nrf2 signaling may play a beneficial role in the treatment of heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nrf2 interacts with Pitx2 to repair heart function by stimulating antioxidant signaling [ 40 ]. However, the dysfunction of Nrf2 induces excessive cardiac oxidative stress, senescence, and cell death [ 41 , 42 ]. Therefore, the activation of Nrf2 signaling may play a beneficial role in the treatment of heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study highlighted that apigenin activates glutathione peroxidase 4 and alleviates ferroptosis and oxidative stress, which is in concordance with our molecular docking results [79]. Furthermore, it has been shown that naringenin alleviates myocardial ischemia/reperfusion injury by regulating the Nrf2/System xc-/GPx4 axis [80], while rutin induces glutathione peroxidase activity in cadmium-induced oxidative stress [81].…”
Section: Discussionsupporting
confidence: 86%
“…Luteolin markedly alleviates myocardial injury and cardiac dysfunction by activating the PI3K/Akt pathway and inhibiting the Siti1/NLRP3/NF-κB and ROS-mediated MAPK pathways [ 67 , 68 ]. In addition, naringenin protects against MIRI by regulating the NRF2/System xc-/GPX4 axis and cGMP-PKGIα signaling pathway [ 69 , 70 ]. Other compounds of O. falcata such as 7-hydroxyflavone and isoliquiritigenin also exert anti-inflammatory and antioxidant effects and can attenuate diabetic cardiomyopathy [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%